Rethinking the concept of economic man and its relevance to the future of Islamic economics - Mohd Yusop, Mohd Mahyudi (IIUM Press, 2016)
This study sheds light on the philosophical underpinnings of Islamic economics, especially its version of a social and moral economic system. The prospect of value-laden economics, the gap between the theory and practice of the Islamic economic system, and an epistemological exposition on the observed gap are discussed. On the first aspect, the study indicates that the future for Islamic economics as one alternative of a value-based approach is indeed promising with the ongoing replacement of Robbin’s fact/value dichotomy with Putnam’s entanglement of fact and value notion. Interestingly, the widely reported gap, in the form of non-achievement of social goals, has led the study to identify a serious flaw in the micro-foundational aspect of Islamic economics; one that has not been noticed before. A more holistic reading of the Qur’ān could solve this micro-foundation issue. Therefore, the study calls for a fresh epistemological approach in Islamic economics methodology that could set in motion a renewed interest in the Islamic economic system discourse.